How Does the Proverb in Sumbang Duo Baleh Represent Minangkabau Culture? - Kania, Annisa Nurhijatul (PAROLE: Journal of Linguistics and Education, 2024)
Minangkabau people are a native group that lives in West Sumatra, which is in the middle highlands of Indonesia. Its spoken language is Minangkabaunese which there are many oral literatures in the language including proverbs. This study aimed to look the forms of the proverbs and the cultural values represented in proverbs use and to figure out the women portrayal represented in proverbs use in Minangkabau’s customary rules: Sumbang Duo Baleh. Cognitive Linguistics theory and Conceptual Metaphor theory were applied in the study to give a complete look at how the community expects women to behave. The results showed that because of Minangkabau women’s importance as leaders and role models in their society, they should fulfil all the social requirement to be become a well-regarded member of society otherwise they will be looked down upon in society.